The Influence of Brand Image, Promotion, and Location on Saving Decisions at Bank Syariah Indonesia Makassar - Nur Annisa; Siti Fatimah; Trimulato (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to analyze the effect of brand image, promotion, and location partially or simultaneously and which of the three factors has the most influence on the saving decision of Bank Syariah Indonesia customers in Makassar City. This research is a quantitative research with a correlational approach. The type of data and data sources used are primary data obtained through questionnaire tabulation of 71 respondents who are customers of Bank Syariah Indonesia in Makassar City. The data analysis method used is multiple linear regression analysis. The results of the study reveal that brand image, promotion, and location partially or simultaneously have a positive and significant effect on the saving decisions of Bank Syariah Indonesia customers in Makassar City. Furthermore, the brand image with the largest coefficient of influence and significant value is the factor that most influences the saving decision of Bank Syariah Indonesia customers in Makassar City. This research is expected to be able to provide information to Bank Syariah Indonesia and other parties regarding which factors have the greatest influence on the decision to save at Bank Syariah Indonesia